Health Sector Reform in Bolivia : A Decentralization Case Study - World Bank (Washington, DC, 2013)
Bolivia made progress in health status and equity in the last decade, thanks to the implementation of a series of health policies directed primarily at reducing maternal and infant mortality and controlling communicable diseases. These policies include the introduction of a focus on health outcomes in the context of decentralization, the implementation of a public health insurance, the strengthening of vertically-financed public health programs and to a lesser extent, an increase in the size of the sector's workforce and greater participation of indigenous peoples for health. This report analyzes these policies, draws lessons from their implementation, discusses remaining challenges, and provides recommendations in the context of the country's latest policy developments. Findings show that while coverage has increased in almost all municipalities, significant equity gaps remain between the rich and the poor, the urban and rural, and the indigenous and non-indigenous. The analysis suggests that the Ministry of Health should concentrate on three key issues: first, maintaining the focus on national priorities in the context of the new, expanded maternal and child insurance; second, strengthening efforts to extend care to poor rural areas; and third, improving the effectiveness of the system in the context of the new management model.